Characterizing flow of pressurized CO2 through micro-orifice for atomization applications: Experiments and CFD modelling - Mohamad Baassiri; Vivek Ranade; Luis Padrela (Journal of CO2 Utilization)
Improving therapeutic efficacy of newly developed drugs remains a major challenge for the pharmaceutical industry. Spray drying based on atomization using high pressure or supercritical CO2 has been shown to be effective in improving therapeutic efficiency of drugs by forming smaller particles, owing to the distinct solvation power and enhanced mixing potential of supercritical CO2. Several parameters contribute to the critical quality attributes of the final atomized pharmaceutical products resulting from CO2-assisted atomization including high-pressure nozzle design, drying chamber geometry, and operating pressures and temperatures. In this context, the work is focused on a detailed analysis of supercritical CO2 through micro-orifices used in a spray drying enhanced atomization process. We present a computational fluid dynamics model, developed using Ansys FLUENT, to describe the flow of pure, pressurized CO2 through a micro-orifice undergoing trans-critical expansion. After establishing grid independence, the computational model was validated by comparing model predictions to measured mass flow rates and temperature distribution of the cooling effect of CO2 free jet over an adiabatic surface. For supercritical inlet conditions and a nozzle orifice size of 80 µm, experimental results matched predictions reasonably well. The simulated results demonstrated the occurrence of shock waves, a prerequisite for fine droplets formation. Simulated results were critically analyzed to develop new insights into intricate fluid dynamics of flow of CO2 through atomization orifices and an attempt is made to evolve specific guidelines. The presented model and results will be useful for researchers and engineers interested in understanding and optimizing CO2-assisted spray atomization processes.